2013
DOI: 10.1371/journal.pone.0058253
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Holistic Processing Predict the Own-Race Advantage in Recognition Memory

Abstract: Individuals are consistently better at recognizing own-race faces compared to other-race faces (other-race effect, ORE). One popular hypothesis is that this recognition memory ORE is caused by differential own- and other-race holistic processing, the simultaneous integration of part and configural face information into a coherent whole. Holistic processing may create a more rich, detailed memory representation of own-race faces compared to other-race faces. Despite several studies showing that own-race faces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
74
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 58 publications
14
74
1
Order By: Relevance
“…The effects obtained here between adaptive coding and face recognition ability were similar in size (small-moderate) to those reported previously between holistic coding and face recognition ability (DeGutis et al, 2013a;Richler et al, 2011;Wang et al, 2012). The effects obtained here between adaptive coding and face recognition ability were similar in size (small-moderate) to those reported previously between holistic coding and face recognition ability (DeGutis et al, 2013a;Richler et al, 2011;Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…The effects obtained here between adaptive coding and face recognition ability were similar in size (small-moderate) to those reported previously between holistic coding and face recognition ability (DeGutis et al, 2013a;Richler et al, 2011;Wang et al, 2012). The effects obtained here between adaptive coding and face recognition ability were similar in size (small-moderate) to those reported previously between holistic coding and face recognition ability (DeGutis et al, 2013a;Richler et al, 2011;Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Previous findings have suggested that dynamic stimuli enhance feature-based processing of faces, which might reduce observers' sensitivity in recognizing own-race and familiar other-race faces (Xiao, Quinn, Ge, & Lee, 2012). Differences in holistic processing are assumed to be one of the key mechanisms of the other-race effect; more specifically, studies have shown that own-race faces were processed more holistically than other-race faces, and that the engagement in holistic processing is associated with higher recognition performance for own-race faces (DeGutis, Mercado, Wilmer, & Rosenblatt, 2013;Michel, Rossion, Han, Chung, & Caldara, 2006;Tanaka, Kiefer, & Bukach, 2004). Furthermore, a previous study revealed that non-rigid motion in dynamic faces is beneficial for the learning of other-race, as well as own-race, faces (Butcher, Lander, Fang, & Costen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one possibility would be if, for a given level of face recognition ability, developmental prosopagnosic subjects had scores on a measure that were clearly different from that predicted from the variation in performance of the normal population (Figure 2). However, the individual differences in face-related measures in the healthy population and how these co-vary with normal face recognition skills are only just beginning to be studied (Degutis, Mercado, Wilmer, & Rosenblatt, 2013; DeGutis, Wilmer, Mercado, & Cohan, 2013). Caution is also required with some of these observations: it may be that certain anomalous phenomena could reflect adaptive strategies that any subject who struggles with face processing – including those just bad at faces - might use.…”
Section: Other Aids To Diagnosismentioning
confidence: 99%